Application of Semiconductor Technology for Piezoelectric Energy Harvester Fabrication - Andrzej Kubiak; Nataliia Bokla; Tamara Klymkovych; Łukasz Ruta; Łukasz Bernacki (Energies)
In this paper, we propose the application of semiconductor technology processes to fabricate integrated silicon devices that demonstrate the piezoelectric energy harvesting effect. The harvesting structure converts thermal energy into electricity using a piezoelectric transducer, which generates electrical signals owing to the dynamic bending under pressure caused by the explosive boiling of the working fluid within the harvester. The challenges of previous works that included complex manufacturing processing and form limitations were addressed by the use of semiconductor technology based on laser beam processing, which led to simplification of the device’s fabrication. The electrical characterization of the fabricated harvester prototype proved its functionality in energy conversion and potential for integration with a step-up converter or power management integrated circuit (PMIC) generating stable impulses ranging from 0.4 to 1.5 V at a frequency of 7 Hz.